Pelatihan Pembuatan Daftar Check List Deteksi Tumbuh Kembang Anak Usia Dini Berbasis Tauhid bagi Guru TK/PAUD Kota Sungai Penuh - Yandri, Hengki; Juliawati, Dosi (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The social service activities are carried out based on basic play group /kindergarten teachers that must have assessment skills to detect the growth of their students. The purpose of this activity was to increase the skills of play group/kindergarten teachers in preparing and making a checklist for detection the growth of childhood on based of Tauhid. The method of this activity was done by the steps; (1) the delivery, (2) the implementation and (3) the termination, with 80 participants of play group/ kindergarten teachers. The results of this activity showed that kindergarten/play group teachers have been basic skills in preparing and making a checklist detection of early childhood on based of Tauhid.